2017
DOI: 10.1007/s12094-017-1722-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeted next-generation sequencing identifies clinically relevant mutations in patients with chronic neutrophilic leukemia at diagnosis and blast crisis

Abstract: The diagnostic utility of a targeted next-generation sequencing approach was clearly demonstrated with the identification of additional mutations providing the potential for therapeutic stratification of chronic neutrophilic leukemia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…Langabeer et al initially reported next generation sequencing (NGS) results from a modest but informative cohort of four CSF3R T618I‐mutated CNL patients, identifying additional mutations in all subjects as follows: SRSF2 (n = 4/4), SETBP1 (n = 3/4), NRAS (n = 1), and CBL (n = 1) . Zhang et al very recently published pivotal results of comprehensive genomic and transcriptomic profiling of 158 cases of neutrophilic leukemias of ambiguous diagnosis, including 39 patients with CNL (the remainder consisting of aCML, MPN‐unclassified, MDS/MPN, and ambiguous diagnosis) .…”
Section: Molecular Pathogenesissupporting
confidence: 89%
See 2 more Smart Citations
“…Langabeer et al initially reported next generation sequencing (NGS) results from a modest but informative cohort of four CSF3R T618I‐mutated CNL patients, identifying additional mutations in all subjects as follows: SRSF2 (n = 4/4), SETBP1 (n = 3/4), NRAS (n = 1), and CBL (n = 1) . Zhang et al very recently published pivotal results of comprehensive genomic and transcriptomic profiling of 158 cases of neutrophilic leukemias of ambiguous diagnosis, including 39 patients with CNL (the remainder consisting of aCML, MPN‐unclassified, MDS/MPN, and ambiguous diagnosis) .…”
Section: Molecular Pathogenesissupporting
confidence: 89%
“…Other reports have evaluated clonal evolution in CNL . Langabeer et alʼs NGS study identified clonal evolution in all patients at blast transformation documented by increasing CSF3R T618I allele frequency or gain/loss of mutations . Karyotypic aberrations in the form of acquisition of monosomy 5 and 7 were noted in a case of CNL with blast transformation .…”
Section: Molecular Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…This has changed with the discovery of oncogenic mutations in the colony‐stimulating factor 3 receptor gene ( CSF3R ) in the majority of patients with CNL reported in a landmark study by Maxson et al in 2013 . This observation was subsequently validated in multiple other case series of WHO‐defined CNL . The knowledge of the molecular pathways involved in disease pathogenesis allows for the development of molecularly targeted therapy, the potential of which has since confirmed through in vitro , animal models and anecdotal clinical evidence and leading to the first multicenter clinical trial for CNL which is currently enrolling (http://clinicaltrials.gov‐study ID = 02092324) …”
Section: Disease Overview and Diagnosismentioning
confidence: 78%
“…In that data set of WHO‐defined CNL, the median age at diagnosis was 66 years (range: 15 – 86) and 56% were male . With the discovery of CSFR3 mutations in CNL, comes the opportunity for greater accuracy in true CNL diagnosis: we performed s review of the literature from that point on (2013) and identified a total 57 reported cases of CSF3R ‐mutated CNL, the majority (88%) carrying the CSF3R T618I mutation . The median age (range) was 65 years (10–92) and 70% were male.…”
Section: Epidemiology and Demographicsmentioning
confidence: 99%